The evolution of innovation networks: The case of a German automotive network - Tobias Buchmann; Andreas Pyka (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2013)
In this paper we outline a conceptual framework for depicting network development patterns of interfirm innovation networks and for analyzing the dynamic evolution of an R&D network in the German automotive industry. We test the drivers of evolutionary change processes of a network which is based on subsidised R&D projects in the 10 year period between 1998 and 2007. For this purpose a stochastic actor-based model is applied to estimate the impact of various drivers of network change. We test hypotheses in the innovation and evolutionary economics framework and show that structural positions of firms as well as actor covariates and dyadic covariates are influential determinants of network evolution.
urn:nbn:de:bsz:100-opus-8338
Keywords: 330